Readiness to Screen for Domestic Violence against Women in Healthcare Uganda: Associations with Demographic, Professional and Work Environmental Factors - Lawoko, Stephen; Ochola, Emmanuel; Oloya, Geoffrey; Piloya, Joyce; Lubega, Muhamadi; Lawoko-Olwe, Winnie; Guwatudde, David (Open Journal of Preventive Medicine, 2014)
We assessed demographic, professional and work environmental determinants of readiness to screen for Intimate Partner Violence among healthcare practitioners in healthcare Uganda. Methods: The Domestic Violence Healthcare Provider Survey Scale and the Demand-Control-Support questionnaire was administered to a random sample of 376 health care providers (n = 279 valid responses) from Gulu, Anaka, Lacor and Iganga hospital situated in northern and eastern Uganda. Correlation tests, t-tests, ANOVA and Multiple Linear regression were used to analyse the data. Results: Male care providers were more likely than female peers to blame the victim for the occurrence of Intimate Partner Violence in a relationship. Participants from Lacorhospital graded a lower self-efficacy and a poorer support network with regard to screening for Intimate partner violence, and a higher propensity to blame the victim when contrasted with other hospitals. Doctors experienced a lower self-efficacy with regard to IPV screening than other professions. Blaming the victim for abuse was associated with a high work load and low support at work. In addition, with increasing work control and support, participants’ appraisal of system support and self-efficacy increased. Conclusion: Gender, profession, facility of work, work demand, control and support are important determinants of the readiness to screen for IPV in healthcare Uganda, and should inform strategy for the introduction and implementation of routine IPV inquiry in healthcare Uganda.
Keywords: Screening; Domestic Violence; Women; Healthcare; Uganda; Determinants